Quality parametres of four types of formulations based on Trichoderma asperellum and Purpuricillium lilacinum - Viera, William; Noboa, Michelle; Bermeo, Johana; Báez, Francisco; Jackson, Trevor (Enfoque UTE, 2018)
The genus Trichoderma and to a lesser extent Purpureocillium, have been studied extensively for their properties as beneficial microorganisms and their effectiveness in disease control. However, biological efficacy is not the only parameter considered when formulating a microorganism; viability, purity and concentration in the formulation are important characteristics to ensure success in the field. The aim of this study was to access different types of formulations (granules, powders, liquids) to record their behavior over time, using the variables viability, concentration and purity to select best formulations based on these parameters. As a result, it was obtained that the bioformulates based on T. asperellum showed greater stability during storage, with dry solid formulations being more stable in comparison with liquid products. In terms of the P. lilacinum formulations, it was observed that the presentation of wettable powders showed the highest concentration and stability over the time.